Inhaler Technique and Self-reported Adherence to Medications Among Hospitalised People with Asthma and COPD - Astrid Elander; Maria Gustafsson (Adis, Springer Healthcare, 2020)
Abstract Background Metered dose inhalers (MDIs) and dry powder inhalers (DPIs) are devices used for the treatment of asthma and chronic obstructive pulmonary disease (COPD). Inhaler technique is important since incorrect technique can lead to a poorer prognosis and hospitalization. Objective The objective of this study was to investigate the inhaler technique and overall adherence to medications in an adult population with asthma and COPD. Patients and Methods Those invited to participate were people admitted to Umeå University Hospital in northern Sweden in October, November and December 2018, with inhaled medication prescribed prior to admission. Inhaler technique was assessed using checklists and observations with placebo-inhalers were conducted. The Medication Adherence Report Scale (MARS)-5 was used to measure self-reported overall adherence to drug medication. Results Of the 23 people included in the study, 26.1% had one or more critical errors in inhaler technique and 30.4% were considered overall non-adherent to drug medication. Among the 23 participants, the mean age, and the number of regularly prescribed medications were higher among those with poor inhaler technique than among people with no error in their inhaler technique. Conclusion This study indicates that poor inhaler technique and overall non-adherence to medications occur among hospitalised people with asthma and COPD living in northern Sweden. Interventions to improve inhaler technique and adherence to drugs are needed.